Cultural conceptualization of death in religious and carnival worldviews in Middle English - Shevchenko, Iryna; Morozova, Iryna (Lesya Ukrainka Volyn National University, 2025)
This study explores the cultural conceptualization of DEATH within two contrasting medieval worldviews -- the religious/moral and the carnival -- through the lens of Cultural Linguistics. Drawing on English literary texts from the 14th to 17th centuries, the paper analyzes how DEATH was perceived, framed, and emotionally coded in different sociocultural paradigms. Using the theoretical framework of Cultural Linguistics, which regards language as a reflection of culturally embedded cognition, the research identifies distinct cultural schemas, such as DEATH IS NATURAL TERMINAL, DEATH IS DIVINE PREORDINATION, DEATH IS MORAL EQUALIZER, and DEATH IS RELIEF/REST -- in the religious worldview. These schemas present DEATH as a natural, moral, or divine event, often met with passive acceptance or spiritual reflection. In contrast, the carnival worldview re-negotiates DEATH as grotesque and laughable, with schemas like DEATH IS OBJECT OF RIDICULE, exemplified by parodic and humorous depictions in comedy. The study applies both onomasiological and componential analyses to identify the semantics of DEATH-related lexemes and traces its re-conceptualization in literary discourse. Ultimately, the research illustrates how DEATH, though a universal human concern, is cognitively constructed in culturally variable ways, revealing evolving ideological, ethical, and aesthetic orientations. The findings contribute to broader understanding of how historical-cultural conditions shape emotional and metaphorical frameworks in the worldview.
Keywords: cultural schemas; metaphorical cognition; cultural linguistics; 'death' conceptualization; medieval worldview; religious vs carnival ethics